Autophagy in Plasma Cell Pathophysiology - Oliva, Laura; Cenci, Simone (Frontiers in Immunology, 2014)
Plasma cells are the effectors responsible for antibody-mediated immunity. They differentiate from B lymphocytes through a complete remodeling of their original structure and function. Stress is a constitutive element of plasma cell differentiation. Macroautophagy, conventionally referred to as autophagy, is a conserved lysosomal recycling strategy that integrates cellular metabolism and enables adaptation to stress. In metazoa, autophagy plays diverse roles in cell differentiation. Recently, a number of autophagic functions have been recognized in innate and adaptive immunity, including clearance of intracellular pathogens, inflammasome regulation, lymphocyte ontogenesis, and antigen presentation. We identified a previously unrecognized role played by autophagy in plasma cell differentiation and activity. Following B cell activation, autophagy moderates the expression of the transcriptional repressor Blimp-1 and immunoglobulins through a selective negative control exerted on the size of the endoplasmic reticulum and its stress signaling response, including the essential plasma cell transcription factor, XBP-1. This containment of plasma cell differentiation and function, i.e., antibody production, is essential to optimize energy metabolism and viability. As a result, autophagy sustains antibody responses in vivo. Moreover, autophagy is an essential intrinsic determinant of long-lived plasma cells in their as yet poorly understood bone marrow niche. In this essay, we discuss these findings in the context of the established biological functions of autophagy, and their manifold implications for adaptive immunity and plasma cell diseases, in primis multiple myeloma.